Slops for the Tarpaulin Rabble : The Clothing of Anglo-American Sailors 1680-1740 - Fictum, David (East Carolina University, 2015)
This thesis defines and examines the clothes common rank Anglo-American sailors wore in the 1680 to 1740 period and concentrates on insights their attire can provide into their behaviors to provide a deeper understanding of their lives within the context of the greater maritime society and culture. This work fills in previously neglected gaps in the study of Anglo-American maritime clothing and early maritime history. Through examining maritime clothing, maritime studies gains new perspectives into maritime life not previously attained through other more traditional methods of studying the social history of sailors.
Keywords: History; British Royal Navy history; Clothing history; Maritime social history; Material culture; Pirate history; Merchant mariners--Clothing--Great Britain--17th century; Merchant mariners--Clothing--Great Britain--18th century